Romantyzm krańców Europy. Portugalia, Polska i Chrystus narodów - Łukaszyk, Ewa A. (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2021)
This article tentatively provides acomparative outlook on Polish and Portuguese Romanticism. Taking as a starting point the famous parallel between the opposite ends of Europe sketched by the 19th-century historian Joachim Lelewel, the author claims that Polish and Portuguese literature, although they had almost no direct contact with each other, participated in the same system of cultural coordinates established by European Romanticism. At the same time, both nations had some sort of dispute or clash with Europe, developing syndromes of inferiority, as well as megalomaniac visions of their moral superiority. Almeida Garrett and Alexandre Herculano tried to provide a solution, harmonising their country with its European context. The conclusion accentuates the uttermost victory of this harmonising vision, presenting the contemporary Portuguese culture as fully Europeanised and contrasting it with the doubts concerning European identity that may be observed in contemporary Poland.